2014
DOI: 10.1002/hbm.22584
|View full text |Cite
|
Sign up to set email alerts
|

BDNFVal66Met genotype interacts with childhood adversity and influences the formation of hippocampal subfields

Abstract: Childhood stress and genetic factors like the Val66MET polymorphism of the brain derived neurotrophic factor (BDNF) gene are associated with a higher risk for developing major depressive disorder (MDD) and might also influence hippocampal changes. The aim of this study was to determine which hippocampal dentate gyrus and cornu ammonis subfields are altered in MDD compared to healthy controls and which subfields are affected by the BDNF Val66Met polymorphism and child adversity. Adult patients with MDD and heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
38
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 42 publications
5
38
1
Order By: Relevance
“…Moreover, gross volumetric differences might not be as sensitive as effects on subregions. For instance, a recent study in adults reporting histories of childhood trauma found trauma-by-BDNF effects on specific subregions of the hippocampus (i.e., CA2/3; Frodl, Skokauskas et al 2014). Continued research will address regional specificity and cellular changes that underlie structural MRI GMV differences, and will contribute understanding to how BDNF modulates limbic brain structures over the course of development.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, gross volumetric differences might not be as sensitive as effects on subregions. For instance, a recent study in adults reporting histories of childhood trauma found trauma-by-BDNF effects on specific subregions of the hippocampus (i.e., CA2/3; Frodl, Skokauskas et al 2014). Continued research will address regional specificity and cellular changes that underlie structural MRI GMV differences, and will contribute understanding to how BDNF modulates limbic brain structures over the course of development.…”
Section: Discussionmentioning
confidence: 99%
“…This is a functional SNP that reduces the processing of pro-BDNF to mature BDNF decreases BDNF transport to terminals, and thereby blocks activity dependent release of BDNF. The BDNF Met allele has been associated with reduced hippocampal volume and executive function in humans [28, 29] and increased risk for depression in patients exposed to early life stress or trauma [32, 45, 54]. BDNF Met knock-in mice display a reduction in the number and length of branch points of CA3 pyramidal neurons in the hippocampus (spine density was not examined) [57].…”
Section: Mechanisms Underlying Dendrite and Spine Deficits Caused By mentioning
confidence: 99%
“…The met-allele of the Val66Met Single-Nucleotide Polymorphism (SNP) of the BDNF gene, coding for a replacement of the amino acid valine (val) by methionine (met), has been associated with decreased activity-dependent secretion of BDNF (Egan et al , 2003; Chen et al , 2004). Previous studies investigating a BDNF gene by CM interaction have shown that Met-carriers of the BDNF gene with a history of CM have decreased volume of the anterior cingulate cortex (ACC) (Gerritsen et al , 2012), hippocampus (Molendijk et al , 2012; Carballedo et al , 2013; Frodl et al , 2014) and amygdala (Gatt et al , 2009) compared to met-carriers without CM and individuals with a val/val genotype, although again results have been inconsistent (Gerritsen et al , 2012). …”
Section: Introductionmentioning
confidence: 99%